2017
DOI: 10.1371/journal.pone.0176182
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 partial agonist MK-2305 lower fasting glucose in the Goto Kakizaki rat via suppression of endogenous glucose production

Abstract: GPR40 (FFA1) is a fatty acid receptor whose activation results in potent glucose lowering and insulinotropic effects in vivo. Several reports illustrate that GPR40 agonists exert glucose lowering in diabetic humans. To assess the mechanisms by which GPR40 partial agonists improve glucose homeostasis, we evaluated the effects of MK-2305, a potent and selective partial GPR40 agonist, in diabetic Goto Kakizaki rats. MK-2305 decreased fasting glucose after acute and chronic treatment. MK-2305-mediated changes in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This possibility is consistent with the lower GIR observed during HGC in 28-30 weeks Gpr120/40KO mice, and is supported by the finding that Gpr120KO mice can develop insulin resistance [3]. However, glucagon secretion and glucagon sensitivity are elevated in Gpr120KO mice [27] and Gpr40 agonist treatment inhibits glucose production in Goto Kakizaki rat through changes in gluconeogenesis [56]. Hence, increased glycogenolysis and gluconeogenesis could also contribute to higher blood glucose levels in Gpr120/40KO mice.…”
Section: Discussionsupporting
confidence: 79%
“…This possibility is consistent with the lower GIR observed during HGC in 28-30 weeks Gpr120/40KO mice, and is supported by the finding that Gpr120KO mice can develop insulin resistance [3]. However, glucagon secretion and glucagon sensitivity are elevated in Gpr120KO mice [27] and Gpr40 agonist treatment inhibits glucose production in Goto Kakizaki rat through changes in gluconeogenesis [56]. Hence, increased glycogenolysis and gluconeogenesis could also contribute to higher blood glucose levels in Gpr120/40KO mice.…”
Section: Discussionsupporting
confidence: 79%
“…MR1704 reduced the plasma glucose excursion in rats unresponsive to glibenclamide treatment. Data from studies on GPR40/FFAR1 synthetic agonists (Chen et al, ; Lin et al, ; Miller et al, ; Tan et al, ; Tanaka et al, ; Tsujihata et al, , Ito et al, ) have demonstrated that activation of GPR40/FFAR1 can augment insulin secretion. GPR40/FFAR1 is a Gq family G‐protein coupled receptor (GPCR), activation of which promotes the phospholipase C‐mediated hydrolysis of phosphatidylinositol 4,5‐bisphosphate into diacylglycerol and inositol 1,4,5‐triphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…GPR40 is from the class of GPCRs that signal through the Gq pathway. [20][21][22] Therefore, the highly robust Cisbio HTRF IP-1 Gq cell-based assay kit was employed that detects the accumulation of IP-1, a stable downstream metabolite of IP-3 induced by activation of a phospholipase C (PLC) cascade. 3,[23][24][25][26][27] According to the Cisbio IP-1 instructions, the kit allows direct characterization of all types of compounds acting on Gq-coupled receptors in either adherent or suspension cell assays.…”
Section: Methods For Medium Exchangementioning
confidence: 99%